Beekeeping for dummies ebook - Blackiston, Howland (2020)
The single best and most comprehensive guide for prospective, new and experienced hobbyist beekeepers Beekeeping For Dummies, 5th Edition , is one of the most popular titles in the For Dummies series available today. Including the latest information regarding every aspect of backyard beekeeping and honey production, this book describes how to get started, how to care for and safely handle bees, and how to maintain healthy and productive colonies. This book is loaded with up-to-date, practical examples and helpful illustrations of proven techniques and strategies for both new and seasoned hobbyist beekeepers. Some of the updates for this brand-new edition include: New information regarding the critical role that nutrition plays in the health and productivity of your bees News about the latest beekeeping products, medications, and all-natural remedies Information regarding dozens of helpful beekeeping resources Redeemable coupons from beekeeping suppliers that save the reader money Beekeeping For Dummies embodies the straightforward and simple approach made famous by the For Dummies series. Each and every reader will benefit from its accessible and approachable take on beekeeping.